Gender-Based Verbal Violence and Strategies to Address It in School - Sutinah; Sudarso; Dimas Ramadhiansyah; Pingkan Sekar Savira; Rafi Aufa Mawardi (Airlangga University, 2026)
School has always been one of the most vulnerable locations for gender-based verbal violence. The quality of the learning climate in school is not only determined by the teaching staff but also by the students. As one of the leading schools in Ponorogo Regency, 3 State Senior High School Ponorogo is not immune to the practice of gender-based verbal violence, which the school is currently working to eliminate. This study aims to explore the forms of, the levels of students’ understanding and awareness about, and strategies that can be implemented to reduce gender-based verbal violence. A mixed research method was used, involving 50 student participants. Data collection was conducted through pre-test and post-test surveys with 50 students and focus group discussions with 10 selected students. This study found that the practices of gender-based verbal violence are normalized through racist taunts, misogynistic jokes, and gender-stereotypical expressions among students. The survey results showed that participants were still lacked understanding and awareness of gender-based verbal violence in the school environment, but their awareness and understanding increased after participating the socialization session. These findings suggest the need for structured and contextualized education to build a safe, inclusive, and gender-equitable school climate.Keywords: Verbal violence; Gender-based violence; Symbolic violence; School violence; Gender equality